Understanding Age‐Induced Cortical Porosity in Women: The Accumulation and Coalescence of Eroded Cavities Upon Existing Intracortical Canals Is the Main Contributor. (4th January 2018) - Andreasen, Christina Møller; Delaisse, Jean‐Marie; van der Eerden, Bram CJ; van Leeuwen, Johannes PTM; Ding, Ming; Andersen, Thomas Levin
ABSTRACT: Intracortical bone remodeling normally ensures maintenance of the cortical bone matrix and strength, but during aging, this remodeling generates excessive porosity. The mechanism behind the age‐induced cortical porosity is poorly understood and addressed in the present study. This study consists of a histomorphometric analysis of sections of iliac bone specimens from 35 women (age 16–78 years). First, the study shows that the age‐induced cortical porosity reflects an increased pore size rather than an increased pore density. Second, it establishes a novel histomorphometric classification of the pores, which is based on the characteristics of the remodeling sites to which each pore is associated. It takes into consideration (i) the stage of the remodeling event at the level where the pore is sectioned, (ii) whether the event corresponds with the generation of a new pore through penetrative tunneling (type 1 pores) or with remodeling of an existing pore (type 2 pores), and (iii) in the latter case, whether or not the new remodeling event leads to the coalescence of pores. Of note, the advantage of this classification is to relate porosity with its generation mechanism. Third, it demonstrates that aging and porosity are correlated with: a shift from type 1 to type 2 pores, reflecting that the remodeling of existing pores is higher; an accumulation of eroded type 2 pores, reflecting an extended resorption‐reversal phase; and a coalescence of these eroded type 2 pores into enlarged coalescing type 2 cavities. Collectively, this study supports the notion, that age‐related increase in cortical porosity is the result of intracortical remodeling sites upon existing pores, with an extended reversal‐resorption phase (eroded type 2 pores) that may likely result in a delayed or absent initiation of the subsequent bone formation. © 2017 The Authors. Journal of Bone and Mineral Research Published by Wiley Periodicals Inc.